Experimental and Numerical Investigation on Behavior of Rectangular Closed Section Steel Truss Beams with Concrete-Filled Joints - He, Junlong; Kong, Fanlei; Huang, Pingming; Mei, Kuihua (Buildings (Basel), 2024)
This study investigates the flexural performance of steel trusses with concrete infill and gradient stiffeners at the joints. Three specimens were fabricated and subjected to flexural tests. A finite element model was developed and validated based on experimental results. This model was used to study the stiffness to evaluate the effects of concrete infill and gradient stiffeners at joints on the steel truss. The results demonstrated that all three specimens were subjected to joint tensile–compression failure. The ultimate bearing capacity of specimens with concrete infill and stiffening ribs increased by 29.7% and 35.6%, respectively. The displacement deformation of joints decreased by 21.6% and 18.9%, respectively, and the initial stiffness increased by 31.3% and 39.1%, respectively. Therefore, the concrete infill significantly enhanced the ultimate bearing capacity and flexural stiffness of the steel truss while reducing slip deformation at the joints. The concrete infill improved the deformation resistance of the joints and increased the overall stiffness of the structure. Gradient stiffeners had a limited effect on enhancing the ultimate bearing capacity and flexural stiffness but contributed to a smoother stress transition between filled and unfilled sections. This could also reduce stress distortion at the joints.